Ranibizumab in diabetic macular edema - Krispel, Claudia (Baishideng Publishing Group Co., Limited, 2013)
By 2050 the prevalence of diabetes will more than triple globally, dramatically increasing the societal and financial burden of this disease worldwide. As a consequence of this growth, it is anticipated that there will be a concurrent rise in the numbers of patients with diabetic macular edema (DME), already among the most common causes of severe vision loss worldwide. Recent available therapies for DME target the secreted cytokine, vascular endothelial growth factor (VEGF). This review focuses on the treatment of DME using the first humanized monoclonal antibody targeting VEGF that has been Food and Drug Administration-approved for the use in the eye, ranibizumab (Lucentis(®)).